Nutrient Content of Hermetia illucens (Black Soldier Fly) Larvae: A Potential Candidate as Animal Feed - Thiruchenthooran, V.; Mathyamuthan, J.P.; Senthilnanthanan, M.; Surendran, S.N. (University of Jaffna, 2018)
Hermetia illucens larvae are considered as potentials for animal feed with rich nutrition content. The study analyzed nutrient content of the larvae following established protocols to determine moisture, dry matter, ash, crude protein, crude fiber, crude fat, total sugar, calcium and phosphorous of pre-pupae and 4th stage larvae. Further the results were statically compared through t-Test to find the relevant stage. In results, pre-pupa and larvae displayed mainly 47, 41.8 percentage crude protein, 13.4, 7.5 percentage crude fiber, 22, 25.7 percentage crude fat and 19:1, 23:1 calcium and phosphate in ratios as following. Physiological features of other stages expressed inadequate contents comparatively. In conclusion, Hermetia illucens pre-pupa yield comparatively higher nutrition and require addition of extra minerals.
Keywords: Hermetia illucens; Nutrient contents; Animal feed